Фразеология как способ передачи негативных эмоций (на материале фразеологизмов русского и немецкого языков со значением эмоционального состояния человека) - Колесникова, О.В. (Культура народов Причерноморья, 2014)
В статье рассмотрены особенности репрезентации негативных эмоций в русской и немецкой фразеологии. Представлена национальная специфика эмоционального воздействия с учетом когнитивного подхода к описанию языковых единиц. Выявлены основные образы, на которых построены фразеологизмы указанной семантики. Описаны компоненты структуры фразеологических единиц, называющие части тела и органы человека (соматизмы). У статті розглянуто особливості репрезентації негативних емоцій у російській та німецькій фразеології. Представлено національну специфіку емоційного впливу з урахуванням когнітивного підходу до описання мовних одиниць, зокрема - фразеологізмів. Виявлено основні образи, на якіх базуються фразеологізми названої семантики. Описано компоненти структури фразеологічних одиниць, що називають частини тіла та органи людини (соматизми). The article examines the representation of negative emotions in Russian and German phraseology. Presented to the national specificity of the emotional effects including cognitive approach to the description of linguistic units.The basic images which built idioms specified semantics. Describes the components of the structure of phraseological units, naming body parts and organs (somatism), the main ones - head, heart, ears, neck. Display of emotions of anger and rage in a number of cases identified with the killing of an object by reference to deprivation or damage to vital organs. Such components in the structure of EF, as the head, neck, colon, soul, correspond with the anthropic source of culture and designate these bodies. Thus, these components are purchased as a symbol of life and health of the subject. Place of localization of strong emotions is the heart. Rage and anger in the German phraseology is localized in the stomach, which differs from the Russian national ideas. Resentment, sadness is localized in the gras. Idiom describing negative emotions posroeny on the metaphor of "the manifestation of emotions - the upward movement." At the heart of the studied EF is the oldest idea of the spirit, soul and body are opposed to each other. Flesh acts as a "border" between the inner world of man and the surrounding external world.